The subfamily Donaciinae (Coleoptera: Chrysomelidae) in Mexico - Rodríguez-Mirón, Geovanni M.; López-Pérez, Sara (Instituto de Ecología, A.C., 2022)
The subfamily Donaciinae is distinguished from the rest of the leaf beetles by the aquatic larvae and semiaquatic adults. In Mexico, there are records for Donacia Fabricius, Neohaemonia Székessy, and Plateumaris Thomson. The study of this subfamily in Mexico is poor; thus, in the present work, a dichotomic key for the genera distributed in the country, a diagnosis, and photographs for the species are provided, with the objective of providing a tool that facilitates the identification of the Mexican Donaciinae that could be found in collections or in material from recent collects and thus increase the taxonomic and ecological knowledge of this subfamily. In addition, Neohaemonia flohri (Jacoby) is reported for the first time in Tlaxcala.